2022
DOI: 10.1126/sciadv.abq0222
|View full text |Cite
|
Sign up to set email alerts
|

High-specificity protection against radiation-induced bone loss by a pulsed electromagnetic field

Abstract: Radiotherapy increases tumor cure and survival rates; however, radiotherapy-induced bone damage remains a common issue for which effective countermeasures are lacking, especially considering tumor recurrence risks. We report a high-specificity protection technique based on noninvasive electromagnetic field (EMF). A unique pulsed-burst EMF (PEMF) at 15 Hz and 2 mT induces notable Ca 2+ oscillations with robust Ca 2+ spikes in osteoblasts in contrast to other wavef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Tis study gains insights into the mechanism of osteogenic diferentiation that may contribute to new strategies for the prevention and treatment of PMOP and even other metabolic bone diseases (Figure 7). It is reported that PEMF has multiple biological functions in bone metabolism, including promoting osteogenesis, [39,40] attenuating osteoclast activity [41,42], inhibiting cellular infammation [43,44], etc. PEMF is also a novel potential physiotherapy to promote osteogenesis and has attractive traits including good safety, noninvasiveness, low cost, and easy operation [15].…”
Section: Discussionmentioning
confidence: 99%
“…Tis study gains insights into the mechanism of osteogenic diferentiation that may contribute to new strategies for the prevention and treatment of PMOP and even other metabolic bone diseases (Figure 7). It is reported that PEMF has multiple biological functions in bone metabolism, including promoting osteogenesis, [39,40] attenuating osteoclast activity [41,42], inhibiting cellular infammation [43,44], etc. PEMF is also a novel potential physiotherapy to promote osteogenesis and has attractive traits including good safety, noninvasiveness, low cost, and easy operation [15].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal waveform and parameter regimen for a particular site of fracture, as well as the electromagnetic field sensation and signalling mechanisms in osteoblasts, remain unclear. Therefore, further exploration of these parameters and mechanisms is required to guide clinical treatment ( Maziarz et al, 2016 ; Yan et al, 2022 ).…”
Section: Research Progress On Pemf Applications In Bone Repairmentioning
confidence: 99%
“…For this aspect, there are multiple related reviews where people can find more information. [9][10][11] For SMFs, although they have not been FDA-approved, there are also quite a few reports related to its potential application in bone regeneration (Table I), which show that SMFs have multiple beneficial effects on the bone systems both in vitro and in vivo.…”
Section: Bone Regenerationmentioning
confidence: 99%